Formulation and in vitro characterization of alginate microspheres loaded with diloxanide furoate for colon- specific drug delivery - Shukla, Shailendra; Jain, Deepak; Verma, Kavita (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of the research work was to develop cystâ€“targeted alginates microspheres of diloxanide furoate (DF) for the effective treatment of amoebiasis. Calcium alginates microspheres of DF were prepared using emulsification method using calcium chloride as a cross-linking agent. Alginate is a natural polysaccharide found in brown algae. Alginates are widely used in the food and pharmaceutical industries and have been employed as a matrix for the entrapment of drugs, macromolecules and biological cells. Alginate microspheres produced by the emulsification method using calcium chloride. Formulations were characterized for particle size and shape, surface morphology, entrapment efficiency, and in vitro drug release in simulated gastrointestinal fluids. XRD and differential scanning calorimetery were used to confirm successful entrapment of DF into the alginates microspheres. All the microsphere formulations showed good % drug entrapment (73.82Â±1.99). Calcium alginate retarded the release of DF at low pH (1.2 and 4.5) and released microspheres slowly at pH 7.4 in the colon without colonic enzymes.